Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Oxidation of aniline over titania pillared montmorillonite clays - Jagtap, Neelam; Ramaswamy, Veda (Applied Clay Science, 2006)
Titania pillared clays (Ti-PILC) have been synthesized employing conventional stirring (method I) and ultrasonic agitation (method II) techniques followed by hydrothermal treatment. The characterization results revealed the formation of Ti-PILC with significant reduction of time when ultrasonic method was used. Subsequent hydrothermal treatment on the samples has resulted in the increase in the crystallinity and the transformation of anatase TiO2 to rutile TiO2. The rutile phase is more prominent in the samples prepared by stirring method. UV-Vis studies on the samples exhibit blue shift in the absorption band due to the quantum size effect. This indicates that a major part of TiO2 in the pillared clay could be well below 10 nm in size, which is supported by XRD and the average pore size. The pillared clay catalysts have proved to be promising in aniline oxidation with H2O2, selectively forming azoxybenzene under the working conditions. The aniline conversion and the product distribution largely depended on the catalyst concentration, H2O2 to aniline mole ratio, the nature of the solvent and the oxidant. Higher conversion of aniline and greater selectivity for azoxybenzene was obtained with methanol as the solvent. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: aniline oxidation; Azoxybenzene; hydrothermal treatment; pillared clays

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Support modification to improve the sulphur tolerance of Ag/Al2O3 for SCR of NOx with propene under lean-burn conditions - Jagtap, Neelam; Shubhangi B. Umbarkar; Miquel, Pierre; Granger, Pascal; Dongare, Mohan K. (Applied Catalysis B-Environmental, 2009)
Ag/Al2O3 catalysts with 1 wt% SiO2 or TiO2 doping in alumina support have been prepared by wet impregnation method and tested for sulphur tolerance during the selective catalytic reduction (SCR) of NOx using propene under lean conditions, Ag/Al2O3 showed 44% NOx conversion at 623 K, which was drastically reduced to 21% when exposed to 20 ppm SO2. When Al2O3 support in Ag/Al2O3 Was doped with 1 wt% SiO2 or TiO2 the NOx conversion remained constant in presence of SO2 showing the improved sulphur tolerance of these catalysts. Subsequent water addition does not induce significant deactivation. On the contrary, a slight promotional effect on the activity of NO conversion to nitrogen is observed after Si and Ti incorporation. FTIR study showed the sulphation of silver and aluminum sites of Ag/Al2O3 catalysts resulting in the decrease in the formation of reactive intermediate species such as -NCO, which in turn decreases NOx conversion to N-2. In the case of Ag/Al2O3 doped with SiO2 or TiO2, formation of silver sulphate and aluminum sulphate was drastically reduced, which was evident in FTIR resulting in remarkable improvement in the sulphur tolerance of Ag/Al2O3 catalyst. These catalysts before and after the reaction have been characterized with various techniques (XRD, BET surface area, transmittance FTIR and pyridine adsorption) for physico-chemical properties. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag/Al2O3; Aluminum sulphate; DRIFTS; Selective catalytic reduction; Silver sulphate; SiO2; Sulphur tolerance; TiO2

NO reduction under diesel exhaust conditions over Au/Al2O3 prepared by deposition-precipitation method - Miguel, P.; Granger, P.; Jagtap, Neelam; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dujardin, Christophe (Journal of Molecular Catalysis A-Chemical, 2010)
Gold supported on alumina was prepared by urea deposition-precipitation method and compared to silver supported on alumina for the selective catalytic reduction of NO by hydrocarbons under lean conditions. The catalyst showed activity in the reduction of NO and 100% selectivity towards N-2 in the temperature range 300-350 degrees C. At higher temperature the NO conversion decreased due to competitive oxidative reactions of the reductants. XPS analysis confirmed the good stability of gold nanoparticles deposited on alumina. Infrared studies showed the formation of various adsorbed species (formates, carboxylates, ad-NOx and cyanide) on the catalyst surface. Addition of H-2 to the feed containing decane enhanced the formation of these species on the catalyst surface as well as the catalytic activity for the NO conversion to N-2. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Deposition-precipitation; Gold; In situ IR; NO reduction; XPS

Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance